Immunization with vaccinia virus recombinants that express the surface glycoproteins of human parainfluenza virus type 3 (PIV3) protects patas monkeys against PIV3 infection. - Spriggs, M K (1988)
Patas monkeys (Eryphrocebus patas) were immunized intradermally with two vaccinia virus recombinants that individually express the hemagglutinin-neuraminidase glycoprotein or the fusion glycoprotein of human parainfluenza virus type 3 (PIV3). These immunizations induced a high titer of PIV3 serum-neutralizing antibodies. At 1 month after immunization, monkeys were challenged intratracheally with PIV3. Subsequent virus replication was reduced in these monkeys by 3.2 log10 and 1.9 log10 (mean peak virus titers) in the upper and lower respiratory tracts, respectively, compared with control animals. The average duration of virus shedding was also reduced from 9.0 to 3.4 days in the upper respiratory tract and from 5.3 to 1.2 days in the lower respiratory tract. These findings demonstrate that a single intradermal dose of live recombinant vaccinia viruses can significantly restrict the replication of a virus which primarily infects the epithelial cells of the respiratory tract.